2012
DOI: 10.5430/ijfr.v3n2p105
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Factors of Emerging Stock Market: The Evidence from Thailand

Abstract: This paper aims to examine the importance of macroeconomic factors to determine the performance of stock market. The regression analysis is used to examine this relationship. The result shows that macroeconomic variables can explain stock return significantly after adjusting for some lags of data availability. Moreover, the lead-lag relationship is examined by Vector Autoregression model and Granger causality test. They reveal that macroeconomic variables are less important to predict future stock return where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Many studies have shown that macroeconomic variables can be used to explain future stock returns (Asai & Shiba, 1995;Hondroyiannis & Papapetrou, 2001). However, some studies have shown the reverse of this relationship, as stock returns can be use to predict future macroeconomic variables (Tangjitprom, 2012). One example of this relationship is from the study of Henry, Olekalns, and Thong (2004), who have employed a non-linear model to show evidence from 27 countries that stock returns are useful in predicting output growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that macroeconomic variables can be used to explain future stock returns (Asai & Shiba, 1995;Hondroyiannis & Papapetrou, 2001). However, some studies have shown the reverse of this relationship, as stock returns can be use to predict future macroeconomic variables (Tangjitprom, 2012). One example of this relationship is from the study of Henry, Olekalns, and Thong (2004), who have employed a non-linear model to show evidence from 27 countries that stock returns are useful in predicting output growth.…”
Section: Discussionmentioning
confidence: 99%
“…Hondroyiannis and Papapetrou (2001) have also documented a similar direction of the relationships for the stock market in Greece. However, Tangjitprom (2012) found the opposite result, as stock returns Granger-cause most macroeconomic variables in Thailand.…”
Section: Dynamic Model and Long-term Relationshipsmentioning
confidence: 94%
“…The examinations explored above are done in various economies, which comprise of both rising and created economies, thus the outcomes fluctuate. Nopphon (2012) was an out and out deviation from the bearing of different examinations while a few different investigations utilized macroeconomic factors regular in the nations they assessed. This examination is completed in Nigeria and the most widely recognized economic indicators among others chosen for this investigation are the swapping scale, loan cost, swelling rate and total national output.…”
Section: Research Gapmentioning
confidence: 99%
“…The studies reviewed above were carried out in different economies, which consisted of both emerging and developed economies, and so the results varied. Nopphon (2012) was an outright deviation from the direction of other studies while several other studies made use of macroeconomic variables common in the countries they reviewed. This study is carried out in Nigeria and the most common macroeconomic factors among others selected for this study are the exchange rate, interest rate, inflation rate and gross domestic product.…”
Section: Research Gapmentioning
confidence: 83%
“…Therefore, the findings differ depending on the economic environment studied, macroeconomic factors used and the time periods covered. Nopphon (2012) study was a total contradiction and deviation from the general belief that macroeconomic variables affect stock market performance. Using Thailand as a case study, the study covered a period from 2001 to 2010 and found that stock return was a better economic indicator that could predict the behavior of macroeconomic variables.…”
Section: Empirical Reviewmentioning
confidence: 93%